Is trust in government associated with farmers' behaviors of farmland transfer? Evidence from China - Gao, Xue; Feng, Huachao (Frontiers in Sustainable Food Systems, 2025)
IntroductionFarmland transfer plays an important role in optimizing the allocation of agricultural resources. In recent years, public intervention through establishing intermediary organizations from local governments has provided a new perspective for analyzing the differences in farmers' behaviors of farmland transfer. However, the effectiveness of public intervention depends on farmers' trust in government.MethodsIn this study, we investigate the impact of farmers' trust in government on their farmland transfer behavior, using data from the China Family Panel Studies (CFPS) and the Probit model.Results and discussionThe results show that trust in government has a significant and positive effect on both farmland transfer-out and transfer-in behaviors, with a stronger effect on transfer-out behavior. The findings have passed robustness tests. The disaggregated analysis shows that farmers who receive government subsidies and use the Internet benefit the most. Further analysis reveals a substitutive relationship between trust in government and interpersonal trust, which are both key components of social trust. Finally, this study provides policy implications to steadily promote public intervention in farmland transfer, pay more attention to farmers' trust in government, and strictly implement the agricultural subsidy policies.